Study of Modal Characteristics of a Geared Rotor System. (2016) - Saxena, Ankur; Parey, Anand; Chouksey, Manoj
Abstract: Modal analysis is used to determine the inherent dynamic characteristics of a system in forms of natural frequencies, damping factors and mode shapes. These parameters are important in the design of a system for dynamic loading conditions. Conventionally, modal analysis is performed with specific commercial tools. On the other hand, modern FEA softwares have good potential to perform modal analysis studies. This work attempts modal analysis using solid elements in ANSYS Workbench of a geared rotor system supported on ball bearings at the ends. This has been carried out to study the natural frequencies in different modes, to predict the direction of whirl of various modes as well as to study Campbell diagram.. In the end, effect of variation in bearing stiffness has been found out on natural frequencies in various modes of the geared rotor system.